Facebook Recruitment and the Protection of Human Subjects. (September 2019) - Kamp, Kendra; Herbell, Kayla; Magginis, William H.; Berry, Donna; Given, Barbara
Social and behavioral scientists increasingly use Facebook to recruit research participants. Given the everchanging social media landscape, it is important to consider the ethical principles of using such a strategy. The aims of this methodological article are to (a) examine Facebook recruitment in light of the ethical principles of the Belmont Report (respect for persons, beneficence, and justice), (b) describe ethical challenges that may be faced in Facebook recruitment, and (c) provide recommendations for researchers interested in adopting this recruitment method. Ethical challenges inherent in Facebook recruitment include selecting subjects fairly, privacy, and data security. Overall, Facebook is a beneficial resource for recruiting participants into research; however, researchers need to be aware of their responsibility in protecting human subjects.